Prevalence and antimicrobial resistance of Streptococcus suis isolated from local pig breeds in Jiangxi Province, China - Tan, Mei-Fang; Liu, Chen-Long; Zhou, Quan-Yong; Wei, Jia-Zhen; Hong, Jia-Wei; Wan, Ming-Chun; Zhang, Feng-Lin; Ji, Hua-Yuan (Frontiers in Veterinary Science, 2025)
IntroductionJiangxi Province possesses abundant genetic resources of local pig breeds, whose effective conservation is essential for maintaining biodiversity and sustainable utilization. Streptococcus suis is an important zoonotic pathogen that continuously threatens swine production systems and public health globally. This study aimed to investigate the epidemiological characteristics of S. suis among local pig breeds in Jiangxi Province.MethodsAn investigation was conducted on the prevalence and antimicrobial resistance profiles of S. suis in six local pig breeds from Jiangxi Province, including Gandong black pig, Hang pig, Ganxi two-end-black pig, Dongxiang spotted pig, Yushan black pig, and Binhu black pig.ResultsA total of 340 porcine nasal swabs were collected from six local pig breeds. 208 S. suis strains were isolated from 187 samples, with an overall isolation rate of 55.0%. The positive isolation rates of the six local breeds were 58.0, 80.0, 71.7, 51.7, 13.3, and 60.0%, respectively. Antimicrobial susceptibility testing revealed that >98% of isolates were susceptible to carbapenems (meropenem and imipenem), followed by doxycycline (71.6%), ceftiofur (65.9%), spectinomycin (64.4%), and amoxicillin (55.8%). High resistance rates were observed for tilmicosin (96.6%), sulfadiazine (92.8%), colistin (89.9%), apramycin (88.9%), chlortetracycline (87.5%), tiamulin (83.2%), and kanamycin (79.8%). 100% of isolates exhibited multidrug resistance, with significant variations in resistance patterns among breeds. Genotypic analysis identified ermB (macrolides), tetL (tetracyclines), and Sul2 (sulfonamides) as the predominant resistance determinants.DiscussionMultidrug-resistant S. suis strains have become widespread among local pig breeds. This study could provide evidence-based guidance for developing effective prevention and control strategies against S. suis infections and protecting valuable genetic resources of indigenous pig breeds.